The growth and structure of the Nigerian economy. (Draft) - Helleiner, Gerald, K.; Nigerian Institute of Social and Economic Research (NISER) (Ibadan: Nigerian Institute of Social and Economic Research (NISER), 1965)
This volume examines the growth of the Nigerian economy between 1900 - 1962.
lje 7/3/19
Arch
Keywords: Economic condictions; Economic history; Nigeria